2003
DOI: 10.5713/ajas.2003.161
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Growth Hormone Gene in 12 Pig Breeds and Its Relationship with Pig Growth and Carcass Traits

Abstract: The polymorphism of the growth hormone gene in 12 pig breeds (total n=475) was detected by PCR-ApaⅠ-RFLP, and allele A (449 bp, 101 bp and 55 bp) or allele B (316 bp, 133 bp, 101 bp and 55 bp) were observed. In these pig breeds, we found that European pig breeds had high frequencies of allele B, while Chinese native pig breeds had high frequencies of allele A. In addition, the role of porcine GH was investigated in 117 Nanchang White pigs and 361 Large Yorkshire pigs. Eight traits about growth and carcass were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Knorr et al (1997) demonstrated significant association of GH genotypes (polymorphism: M17704.1: g.316G>A) with eight carcass fatness traits. Wang et al (2003) showed an association of GH gene polymorphism (ApaI restriction site) with carcass meat content in Yorkshire pigs. In the present study, daily body weight gain was influenced by GH polymorphism (M17704.1: g.316G>A) with the highest value in the CC genotype pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Knorr et al (1997) demonstrated significant association of GH genotypes (polymorphism: M17704.1: g.316G>A) with eight carcass fatness traits. Wang et al (2003) showed an association of GH gene polymorphism (ApaI restriction site) with carcass meat content in Yorkshire pigs. In the present study, daily body weight gain was influenced by GH polymorphism (M17704.1: g.316G>A) with the highest value in the CC genotype pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Paszek et al (1999) found a QTL (SW37-SW467, 58-75 cM) affected the average daily gain between 35-65 kg, in our study, we did not find IGFBP-4 associated with growth rate at different growth stages, but we found that IGFBP-4 associated with body length and other traits such as fore-body weight, bone weight and legs weight, and these traits can reflect the growth status. Meanwhile, GH and IGF1R genes were mapped on SSC12, and many studies found that these two genes affected porcine growth and development (Wang et al, 2003;Wang et al, 2006), so it is important to study the effect of SSC12 on porcine growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the GH gene is highly polymorphic in a variety of livestock animals. Many polymorphisms have been identified in the GH gene of pig (WENJUN et al 2003), bovids (LUCY et al 1993), goat (MALVEIRO et al 2001) and poultry (SHENG-HAI et al 2007;GHELGHACHI et al 2013;ZHANG et al 2014). In ducks, the effect of GH gene polymorphism on important economic traits has been noted (WU et al 2012;.…”
mentioning
confidence: 99%